Dinamika Pelatihan dan Motivasi dalam Meningkatkan Prestasi Kerja - Nur Ihda Muharom Asulthoni (https://journal.metanusantara.com/jenius/index.php/jem, 2024)
In the era of globalisation and digitalisation, organisations are increasingly aware of the importance of training and motivation in improving employee performance. This study aims to explore the dynamics of training and motivation and their impact on employee performance. The type of research used is qualitative with a case study approach, which allows researchers to understand phenomena in depth through the perspective of participants. The main data sources in this research are in-depth interviews with employees and managers in several technology and local companies in Indonesia that have good training programmes and motivation strategies. The purpose of this study is to identify the key factors that influence the effectiveness of training and motivation in improving employee work performance and provide practical recommendations for companies in designing effective training programmes and motivation strategies.The results show that sustainable and structured training programmes and appropriate motivation strategies have a significant impact on improving employee skills, knowledge and work motivation. The combination of effective training and appropriate motivation is proven to provide a more significant increase in work performance compared to the application of one of these factors separately.